Da'wah Strategy in Improving Youth Morality in Lamongan - Kasanah, Siti Uswatun Nur; Ismawati, Zulva; Santoso, Bobby Rachman (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to analyze da’wah strategy through social media toimprove adolescent morality. Where modern means of digitalizationare easy to bring a significant influence in the lives of teenagers. So,using social media for communicative preaching in improving andimproving teenagers' morality, especially teenagers in the Lamongan,is an excellent opportunity for da’I. Social media is a means of da’wahbecause many teenagers have social media accounts that are usedto share their activities. However, many teenagers do not use socialmedia correctly and adequately, causing a lack of morals andmanners. This article utilizes qualitative descriptive methods, namelyobservation and documents as a data collection tool. The results ofthe research obtained are the effectiveness of da’wah strategy through social media as a means of communicative da’wah that canimprove adolescent morale. In addition, communicative social mediada’wah can create a great opportunity for preachers to convey da’wahthat understands and adapts to the times so that the existence ofda’wah can always be spread bringing the teachings of Islam tomankind.